Pengembangan skala hasad (ḤS-8) dalam psikologi Islam - Rusdi, Ahmad (Asosiasi Psikologi Islam (API) Himpsi, 2018)
Envy has been widely studied, but there is no scale of envy in Islamic psychology that is sufficiently tested. A total of 823 respondents were involved in this study. Ḥasad Scale (ḤS-8) consisted of two components that have been tested with exploratory factor analysis, these two components are hatred (al-karah) when others get easement and feel pleasure (al-ḥubb) when others losing easement. Alpha on this scale is α = 0.929 with an omega is Ω = 0.895. The al-karah component has a good reliability (α = 0.90; Ω = 0.895) as well as the al-Ḥubb component (α = 0.947; Ω = 0.968). Items on this scale have a good quality based on total item correlation (0.693-0.911) and good loading factor (0.531-0.980). Confirmatory Factor Analysis found that this scale has a good fit index (CFI = 0.96; GFI = 0.91; AGFI = 0.82; TLI = 0.94). ḤS-8 has good convergent validity, because it deals with the Malicious Envy Scale (r = .536 **) in both the al-karah (r = .470 **) and al-ḥubb aspects (r = .557 **). ḤS-8 also has good discriminant validity because it is not related to the Benign Envy Scale (r = - 128) and Tanāfus Scale (r = .060). ḤS-8 has a good criterion validity because it is negatively related to other relevant criteria, that were general quality of life (r = - 234 **), psychological quality of life (r = -. 188 *), physical quality of life (r = -. 228 **), and Iḥsān Scale (r = -. 307 **) both in the ritual aspect ('Ibādah) (r = -. 210 *), responsible-mu'āmalah (r = -. 261 **), and generosity-mu'āmalah (r = -. 359 **). Further studies are needed to improve the quality of Ḥasad Scale (HS-8).Keywords: envy,hasad, scale, instrument, measurement, Islamic psychology